2019
DOI: 10.1108/ijcthr-03-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Who visits the apartheid museum and why? An exploratory study of the motivations to visit a dark tourism site in South Africa

Abstract: Purpose This paper attempts to fill the gap that exists in research regarding visitor motivations at dark heritage sites. The purpose of this paper is to explore the motivations of visitors to the Hector Pieterson Memorial and Museum (HPMM) as an iconic dark site in South Africa to identify what motivates visitation and which demographic variables may have an influence on these motivators. Design/methodology/approach To achieve the goal of this research, 205 participants completed a self-administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
(62 reference statements)
1
16
0
1
Order By: Relevance
“…A literature review and detailed insight into the relevant findings related to the concept of dark tourism consumption pointed out that the main subjects of the previously conducted studies were mostly focused on a dark tourism motivation and experiences (Çakar, 2020;Mangwane et al, 2019).…”
Section: Dark Tourism and Dark Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review and detailed insight into the relevant findings related to the concept of dark tourism consumption pointed out that the main subjects of the previously conducted studies were mostly focused on a dark tourism motivation and experiences (Çakar, 2020;Mangwane et al, 2019).…”
Section: Dark Tourism and Dark Traitsmentioning
confidence: 99%
“…The seven reasons to visit dark tourism sites are: 1) for better understanding of the conflicts/wars of the 20 th century, 2) out of compassion for victims and survivors of conflicts/wars, 3) to pay tribute to all victims of conflicts/wars, 4) in memory of the victims from my family, 5) because of suggestions and experiences of friends and/or family, 6) to learn and experience something new and 7) out of sheer curiosity. The list of reasons was created based on the previous research on the topic of dark tourism (Çakar, 2020;Mangwane et al, 2019).…”
Section: Spectrum Of Eight Dark Tourism Productsmentioning
confidence: 99%
“…Therefore, emphasize that young adults want exhibitions which are contemporary, topical and related to the latest trends. However, recent research (Mangwane et al, 2019) showed that young people still visit museums to learn about history. Regarding the most common reasons why young people do not visit individual cultural institutions, Mokhtar and Kasim (2011) found that one of the three most common reasons (other than lack of time and interest) is lack of information.…”
Section: Cultural Needs and Preferences Of Different Age Groupsmentioning
confidence: 99%
“…The history of this activity is rather long, yet the scholarly definition was created by Foley and Lennon in mid-nineties (e.g. Mangwane et al, 2019). Besides these terms, also "thanatotourism", "morbid tourism" or "grief tourism" are recognized in the literature (e.g.…”
Section: Museums and Dark Tourismmentioning
confidence: 99%
“…Besides these terms, also "thanatotourism", "morbid tourism" or "grief tourism" are recognized in the literature (e.g. Mangwane et al, 2019). Museums can be dark tourism destinations and one-the Auschwitz-Birkenau State Museum is especially well known around the world (e.g.…”
Section: Museums and Dark Tourismmentioning
confidence: 99%